2016
DOI: 10.1590/2359-3997000000109
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the prevalence of vitamin D deficiency and hip fractures in nursing home residents and independently living elderly

Abstract: Objective: To compare the prevalence of vitamin D deficiency and fracture history in nursing home residents and community-dwelling elderly subjects and to explore the association of vitamin D levels with various characteristics. Materials and methods: Sixty-six nursing home residents and 139 community-dwelling elderly subjects participated. Marital status, medical history, medication including vitamin D supplements, smoking, past fractures were assessed. Weight and height were measured and body mass index calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 31 publications
(38 reference statements)
0
3
0
1
Order By: Relevance
“…[ 48 , 54 ]. Associations between the independent variables and 25(OH)D were expected, according to previous research in middle aged and older populations, for: age [ 49 , 54 ], household income [ 69 ], education [ 49 ], residence [ 70 , 71 ], alcoholic beverages consumption [ 53 , 72 ] physical activity [ 55 , 73 ] self-perceived health [ 54 ], supplement intake [ 55 , 74 ] and BMI [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 93%
“…[ 48 , 54 ]. Associations between the independent variables and 25(OH)D were expected, according to previous research in middle aged and older populations, for: age [ 49 , 54 ], household income [ 69 ], education [ 49 ], residence [ 70 , 71 ], alcoholic beverages consumption [ 53 , 72 ] physical activity [ 55 , 73 ] self-perceived health [ 54 ], supplement intake [ 55 , 74 ] and BMI [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 93%
“…While lower 25-[OH]D levels in institutionalized older persons were associated with hip fractures, falls alone were hardly associated to vitamin D status [ 80 ]. Interestingly, elevated parathyroid hormone (PTH) was inversely correlated with vitamin D status and was the only predictor of hip fractures [ 81 ]. Additionally, accumulating evidence suggests vitamin D deficiency is associated with sarcopenia in elderly women [ 82 ].…”
Section: Resultsmentioning
confidence: 99%
“…2023; 3(2):60-64 gility fractures in PMW affected by secondary hyperparathyroidism [11] . It has been reported that institutionalized individuals show a high prevalence of vitamin D deficiency and secondary hyperparathyroidism, leading to significantly increased hip fracture risk (more than 7 times) in this population [12] . In this context, serum 25(OH)D₃ and parathyroid hormone (PTH) measurement is a useful and cost-effective means of identifying patients at high risk of falls and fractures [13] .…”
Section: Calcifediol In Hip Fracturesmentioning
confidence: 95%